SISTEM INFORMASI PASIEN POSYANDU PADA POSKESDES KALIMAS - Deasy Purwaningtias; panny agustia rahayuningsih; Patina Patina (STMIK KAPUTAMA, 2021)
The Kalimas poskesdes is one of the government agencies engaged in health, the Kalimas poskesdes are under the auspices or working areas of the Snapper river puskesmas, one of the health services routinely carried out by the Kalimas poskesdes is the Posyandu activities which are conducted every month. Data from each posyandu is managed solely by the poskesdes kalimas and then reported to the snapper river puskesmas, baby and toddler data collection still uses bookkeeping while making reports using Microsoft excle is still fairly simple, so it requires a lot of time in making reports due to repeated data recording. To help the data collection process, the Posyandu Patient Information System was created. Posyandu Patient Information System At Kalimas Poskesdes is a web-based information system. Help provide and present information about infants and toddlers patients who do posyandu in the work area of the poskesdes kalimas. Making this information system using the waterfall software development method and the way to collect data is by observing the Kalkesas poskesdes, interviewing staff working at the Kalimas poskesdes, a literature study that supports the theory of problem solving. The software used in making the Posyandu Patient Information System in Kalimas Posasdes Web-Based is XAMPP as a server, MySQL as a database, Sublime Text as a text editor, Chrome as a browser. While the languages used in making this posyandu patient information system are, PHP, HTML, CSS, JavaScript. And to facilitate the creation of the website also uses a codeigniter framework.